SEG Technical Program Expanded Abstracts 2017 2017
DOI: 10.1190/segam2017-17727948.1
|View full text |Cite
|
Sign up to set email alerts
|

Overburden pore-pressure changes and their influence on 4D seismic

Abstract: SummaryChanges in seismic two-way travel time in the overburden can be attributed to pore pressure changes in the underlying reservoir. Since cap rock permeability is very small, these stress changes occur without drainage on short term, which means that, depending on stress path, pore pressure may also change in the overburden. The direct impact of this on 4D seismic has not been thoroughly addressed in the literature. Here, laboratory data with an overburden shale core are presented, showing stress path depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…For the sandy facies, the Skempton A parameter varies between about 0.15 for 0° orientation and up to 0.45 for 90° orientation. Anisotropy effects of the Skempton A parameter have previously been observed for other shales as well (Holt, Bauer and Bakk ).…”
Section: Resultssupporting
confidence: 66%
“…For the sandy facies, the Skempton A parameter varies between about 0.15 for 0° orientation and up to 0.45 for 90° orientation. Anisotropy effects of the Skempton A parameter have previously been observed for other shales as well (Holt, Bauer and Bakk ).…”
Section: Resultssupporting
confidence: 66%
“…According to Cheng (1997), the significance of Equation 6 is that pore pressure can be generated by incremental normal as well as shear stress, the latter being an effect similar to the concept of Skempton's A s parameter. The undrained pore pressure response to an isotropic stress change (∆𝜎 = ∆𝜎 = ∆𝜎 ) is independent of material orientation relative to the symmetry axis, since B ij = B s is expressed as a volume-weighted average of the two invariant components (Holt et al, 2017). However, the undrained pore pressure generated from an anisotropic stress change depends on stress orientation.…”
Section: Poroelastic Theory and Undrained Pore Pressure Generationmentioning
confidence: 99%
“…For other overburden shales, less pronounced dominance of the poroelastic pore pressure parameters B 33 over its in-plane counterpart B 11 may also play a role in decreasing the quality of approximation. However, the comparison of Lista shale with other overburden shales described by Holt et al (2017Holt et al ( , 2018a, Lozovyi and Bauer (2019), Soldal et al (2021) and Duda et al (2022) suggests that Lista's pore pressure parameters lie within a range typical for relatively soft caprock shales (in terms of static moduli and strength). In the case of Lista shale, parameter B 11 = 0.53, parameter B 33 = 1.51 and the ratio between them B 11 /B 33 = 0.35.…”
Section: Discussionmentioning
confidence: 89%
“…Cheng (1997) demonstrated that Skempton's parameters can also be derived from anisotropic poroelasticity. Holt et al (2017) applied this approach for vertically transversely isotropic (VTI) shales and proved experimentally that the value of A S depends on the angle between the direction of axial stress (1)…”
Section: Introductionmentioning
confidence: 99%